Evaluation of salivary gland tumors- clinically radiologically and pathologically: prospective study - Mishra, Namita; Sharma, Neeta (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Salivary gland tumors are difficult to differentiate based solely on clinical presentation or cytological findings due to their overlapping pictures. Often inadequate samples from cytology pose a challenge in preoperative diagnosis. Histopathology is considered the gold standard in diagnosing these tumors. The purpose of this study was to determine clinical, radiological, and cytological findings of these tumors and to assess the accuracy of these results with that of histopathological diagnosis. Methods: Prospectively 52 patients with salivary gland swellings were enrolled between 2007-2009. Cases with inflammatory swelling were excluded from the study. Demographic, clinical history, preoperatively ultrasonography, cytology, and histopathological data were collected and analyzed. Results: Most cases (65.38%) had parotid gland involvement. Benign tumors were common (80.76%) with pleomorphic adenoma as the most common one. Malignant tumors comprised 19.23%. Mucoepidermoid carcinoma and adenoid cystic carcinoma were common malignant tumors. Local swelling was the most common clinical presentation, and no facial nerve involvement was reported. The hard palate was the most common minor salivary gland affected predominantly by benign tumors. The diagnostic accuracy of fine-needle aspiration cytology was 96.15%, followed by clinical and radiological diagnostic accuracy of 92.31% and 86.54%, respectively. Using McNemar’s test, a significant agreement was found between clinical and histological diagnosis (p=0.1336) and between FNAC and histological diagnosis (p=0.4975). Conclusions: Fine needle aspiration cytology is a highly accurate, sensitive, and specific screening technique. It is safe and reliable, though minimally invasive. Ultrasonography-guided cytology along with clinical, and radiological findings could enhance the pre-operative diagnostic accuracy in distinguishing salivary gland tumors.